The Relationship of Work Requiring Heavy Lifting to the Severity of Inguinal Hernia at Prof. Dr. Margono Soekarjo Purwokerto General Hospital for the 2022–2023 Period - Gregorius Christian Hamid; Yonathan Adi Purnomo (ScieClouds Publishing, 2026)
This study examined the association between occupations involving heavy lifting and the severity of inguinal hernia among patients treated at Prof. Dr. Margono Soekarjo Hospital, Purwokerto, during the 2022-2023 period. A retrospective observational analytical study with a cross-sectional approach was conducted using secondary data from hospital medical records. The study included 190 adult patients diagnosed with inguinal hernia who met the inclusion and exclusion criteria. Occupational category was classified into blue-collar and white-collar work, with blue-collar work used as a proxy for regular manual labor and heavy lifting. Hernia severity was categorized into uncomplicated and complicated hernia based on documented clinical diagnosis. Data were analyzed using univariate analysis, Chi-square test, and Odds Ratio estimation with a 95% confidence level. Most patients were male (91.6%) and aged 46-65 years (52.6%). Blue-collar workers accounted for 56.8% of the sample, while white-collar workers accounted for 43.2%. Most patients had uncomplicated hernia (90.0%), while 10.0% had complicated hernia. The bivariate analysis showed a significant association between occupational category and inguinal hernia severity (p = 0.040). Blue-collar workers had approximately 3.1 times higher odds of experiencing complicated inguinal hernia than white-collar workers (OR = 3.145). These findings suggest that physically demanding occupations may be associated with greater clinical severity of inguinal hernia and should receive attention in occupational health screening and surgical referral decisions. However, the retrospective cross-sectional design limits causal inference, and residual confounding remains possible due to incomplete documentation of obesity, smoking, chronic cough, constipation, and comorbidities. Future prospective studies are therefore needed.